Prognostic Value of Glomerular Filtration Rate in Diabetic Patients with Acute Myocardial Infarction - Ailed Elena Rodríguez Jiménez (Medisur)
Background: low glomerular filtration rate is a known poor prognostic factor in acute coronary syndrome, particularly when associated with diabetes mellitus. Objective: to determine the prognostic value of glomerular filtration rate in hospitalized diabetic patients with acute ST-segment elevation myocardial infarction. Methods: a case-series study was conducted in 68 diabetic patients with acute ST-segment elevation myocardial infarction admitted to the Camilo Cienfuegos Hospital in Sancti Spiritus from January 2012 to December 2013. The glomerular filtration rate on admission was estimated using the Cockcroft-Gault equation. Cardiovascular risk factors, clinical and laboratory variables, the ejection fraction and hospital mortality were analyzed. Results: low glomerular filtration rate was associated with a left ventricular ejection fraction <45% at discharge (p = 0.0060) and cardiac complications including arrhythmias, atrioventricular conduction disturbances, reinfarction, postinfarction angina and Killip class ≥ III (p = 0.0000). It was also associated with increased mortality and lower reperfusion rates. Conclusions: estimating the glomerular filtration rate in diabetic patients with acute coronary syndrome at the time of admission provides significant information for prognosis in the acute phase, even in those with normal creatinine values. A glomerular filtration rate less than 53 mL/min increases the risk of suffering an adverse event during hospitalization eight times.